2020
DOI: 10.1080/01434632.2020.1829630
|View full text |Cite
|
Sign up to set email alerts
|

Understanding low outcomes in English language education in Austrian middle schools: the role of teachers’ beliefs and practices

Abstract: The educational disparities that can be found in the English language learning outcomes of middle school students in Austria have gone relatively unexplored in international research. National studies have tended to attribute lower educational outcomes either to students' socioeconomic status or their multilingual background. In this article, we use the theory of intersectionality to shed new light on how educational disparities that run along socioeconomic lines are tightly entangled with beliefs about studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Persistent beliefs and norms about language teaching, such as the 'monolingual myth', continue to form a main obstacle to multilingual teaching practices (Escobar & Dillard-Paltrineri, 2015;Flognfeldt et al, 2020;Inbar-Lourie, 2010), in accordance with Canagarajah (2013) andMeier (2016). Traditional native-speaker ideals are identified in several studies (e.g., Bayyurt et al, 2019;Calafato, 2020a), as well as views about harmful effects of drawing on other languages in English teaching (Calafato, 2020a(Calafato, , 2020bErling et al, 2020Erling et al, , 2021Jakisch, 2014), corroborating the findings from Pfenninger (2014). Further studies confirm the existence of outdated views on language learning, such as the belief that languages must be learned successively (Burner & Carlsen, 2022) and English-only policies motivated by a nativespeaker are ideal (McMillan & Rivers, 2011;cf.…”
Section: Resesarch Question 2 Part I: Teachers' Beliefsmentioning
confidence: 64%
See 1 more Smart Citation
“…Persistent beliefs and norms about language teaching, such as the 'monolingual myth', continue to form a main obstacle to multilingual teaching practices (Escobar & Dillard-Paltrineri, 2015;Flognfeldt et al, 2020;Inbar-Lourie, 2010), in accordance with Canagarajah (2013) andMeier (2016). Traditional native-speaker ideals are identified in several studies (e.g., Bayyurt et al, 2019;Calafato, 2020a), as well as views about harmful effects of drawing on other languages in English teaching (Calafato, 2020a(Calafato, , 2020bErling et al, 2020Erling et al, , 2021Jakisch, 2014), corroborating the findings from Pfenninger (2014). Further studies confirm the existence of outdated views on language learning, such as the belief that languages must be learned successively (Burner & Carlsen, 2022) and English-only policies motivated by a nativespeaker are ideal (McMillan & Rivers, 2011;cf.…”
Section: Resesarch Question 2 Part I: Teachers' Beliefsmentioning
confidence: 64%
“…Findings from surveys of English teachers in Erling et al (2020, 2021) ( n = 162) indicate that a substantial number of teachers disagree that students' L1 should be encouraged to be used in the English classroom and they were less convinced about the benefits of English when learning an additional language than other studies described above indicated. Two of the three teachers in Jakisch (2014) similarly expressed scepticism about the usefulness of building on English when learning additional foreign languages because of characteristics of English compared to other languages.…”
Section: Resultsmentioning
confidence: 98%
“…These findings can be thought provoking for EFL teachers who are involved in the global educational system to reflect on their pedagogical thoughts and deeds. Given the crucial role teachers play in dismantling inequities that hinder students’ development and in closing the academic gap, it is a good sign that equity, as a common concern in the English language teaching area ( Erling et al, 2020 ), has become a long-term pursuit for EFL teachers with equitable visions both at home and abroad. Furthermore, since equity is perceived as an important predictor of students’ self-efficacy ( Daemi et al, 2017 ), this study has important implications for educational experts and policy-makers concerning how to include more voices from culturally and linguistically diverse students and how to verify whether teachers are incorporating equity into their classroom practices ( Riordan et al, 2019 ).…”
Section: Implications and Directions For Future Studiesmentioning
confidence: 99%
“…In the 2019/20 school year, almost 27% of the 1,135,519 students enrolled in schools in Austria had German as an additional language (GAL) -in the city of Vienna the proportion is about 53% (Statistik Austria, 2021). Students with GAL and from migration backgrounds face significant disadvantages in the Austrian educational system (Erling et al, 2020;Herzog-Punzenberger, 2017;Schreiner et al, 2020;Suchań et al, 2019). Based on Austria's low results in PISA 2018, the Austrian Court of Audit released a critique of the education system.…”
Section: Context: German Language Support Classes (Glsc Deutschförderklassen) In Austriamentioning
confidence: 99%